Chapter Guiding at University. The Protagonists' Point of View - lo presti, francesco (Studies on Adult Learning and Education, 2018)
Starting from both an Italian phenomenological perspective and some international works that develop the guidance theme in the direction of 'educational guidance', this chapter will briefly present the aims, instruments, and results of the Parthenope University Research Unit of the PRIN EMP&Co study, which focused on the specific segment of university guidance. The reflection generated by the study provides information and data to identify guidance methods through a pedagogical approach